Measurement of User Satisfaction for SIBISA Application at TK ABA 1 Buduran Sidoarjo with The EUCS method - Suyatno, Dwi Fatrianto; Ardhini Warih Utami; Rahadian Bisma (Universitas Nahdlatul Ulama Surabaya, 2023)
The SIBISA (Sistem Informasi Billing Siswa) application is utilized by parents at ABA1 Kindergarten in Buduran. Developed in 2022 by lecturers from the Informatics Engineering department, this application is designed to help schools manage financial records, particularly those related to tuition fees and other incidental expenses. The End User Computing Satisfaction (EUCS) method is one approach used to evaluate user satisfaction with information systems, including the SIBISA application. This method assesses various factors that influence user satisfaction, such as application performance, ease of use, and reliability. Notably, the SIBISA application is integrated with WhatsApp, facilitating easier communication between parents and the school. After nearly a year of use, our group conducted a user satisfaction survey using the EUCS method to gauge the application's effectiveness. The results indicate that overall user satisfaction with the SIBISA application is at the